A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from coastal hills in Cha-am, peninsular Thailand - Pauwels, Olivier S. G.; Chomngam, Nirut; Larsen, Henning; Sumontha, Montri (Zootaxa, 2020)
We describe Dixonius pawangkhananti sp. nov. from coastal limestone hills in Cha-am District, Phetchaburi Province, peninsular Thailand. The new species differs from all currently recognized Dixonius by the following combination of morphological characters and pattern: maximal known snout-vent length of 42.6 mm; 16 longitudinal rows of dorsal tubercles; 30 to 32 paravertebral scales; 16 longitudinal rows of ventral scales across the abdomen; six precloacal pores in males, no pores in females; a marked canthal stripe; and a sexually dimorphic dorsal pattern consisting of bands (males) or blotches (females). This description brings the number of Dixonius species to ten, with four species endemic to Thailand.